Community Mentoring on the Inorganic Waste Management and Processing - Parmonangan Manurung; Jonathan Herdioko; Irwin Panjaitan (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2024)
The implementation of waste management from upstream (community) by the Yogyakarta City Government has had an impact on the city community, including residents of RW 6 Demangan Sub-district, Gondokusuman District. Communities have limited knowledge and ability to manage inorganic waste independently. Facing these problems, the community needs assistance to increase knowledge and develop the ability to manage inorganic waste. This is important so that the Yogyakarta City Government's goal of achieving zero inorganic waste can be realized. The community service program aims to educate the community through training and workshop in waste management and processing so that it can reduce the production of inorganic waste. Assistance in the form of education, training, and practices in managing and processing inorganic waste needs to be carried out to increase the knowledge and skills of the community so that waste self-management can be realized. The community service results show that the community of RW 06 is able to manage and process waste. However, waste management and processing activities must be carried out consistently so that the target of zero inorganic waste is achieved.